GESTIÓN DE INTERNACIONALIZACIÓN DE LOS PROGRAMAS DE POST GRADO EN CIENCIAS ECONÓMICAS Y EMPRESARIALES - Castillo Maza, Juan Victoriano (2010)
As part of the internationalization process promoted by the Universidad Nacional Mayor de San Marcos (San Marcos University), Units of Graduate Schools of Economics and Administrative Sciences under Interinstitutional Cooperation Agreement with the University Montesquieu Bordeaux IV of France and Universidad Nacional Mayor de San Marcos, with the experience of nearly two decades of improving service delivery of the highest academic level in the Masters and Doctoral programs, are offered in the past five years international masters and doctoral dual degree, with results successful. The Faculty of Economics offers a Masters and PhD in Management Sciences and the Faculty of Management offers the Master program in International Management awarded by the Institute of Business Administration from the University Montesquieu-Bordeaux IV of France and the Masters Training in International Management with a concentration in International Trade or International Finance Unit given by the Graduate School of Management at the Universidad Nacional Mayor de San Marcos (Lima - Peru).